Alpha-defensins determination in different types of synovial fluid and parallel collected serum samples by ELISA - Kušnierová, Pavlína; Bystroňová, Iveta; Walder, Pavel; Hlubek, Rudolf; Všianský, František; Stejskal, David (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2021)
AIMS: The study aims were to verify the serum (S) and synovial fluid (SF) reference intervals (RIs) for human neutrophil defensins (HNP1-3); measure S and SF defensin concentrations in different types of SF, including non-inflammatory, inflammatory non-pyogenic, inflammatory pyogenic, and hemorrhagic; and to compare the HNP1-3 concentrations in SF and S with those of other inflammatory biomarkers. METHODS: SF and S samples were collected from 92 patients. HNP1-3 concentrations were determined using enzyme-linked immunosorbent assays; glucose, lactate, interleukin-6, and procalcitonin using an automatic analyzer; and presepsin using a Pathfast system. There were 61 non-inflammatory, 11 inflammatory non-pyogenic, 11 inflammatory pyogenic, and 9 hemorrhagic SF. Non-inflammatory SF was divided into non-inflammatory normal and non-inflammatory osteoarthritis. The former was used to estimate the HNP1-3 RI in SF and S. RESULTS: The estimated HNP1-3 RIs of SF and S were 12.47-437.42 mg/L and 5.45-44.75 μg/L, respectively. HNP1-3 differed significantly between S and SF and individual groups of SF (P<0.001 and P=0.001, respectively). There were significant relationships between SF HNP1-3 and S HNP1-3 (P<0.001), S C-reactive protein (P<0.001), and S interleukin-6 (P=0.007), and between SF HNP1-3 and SF C-reactive protein (P=0.004) and SF interleukin-6 (P<0.001). The highest kappa coefficient was between SF HNP1-3 and SF interleukin-6 (κ=0.507). CONCLUSIONS: We validated the SF HNP1-3 diagnostic kit and demonstrated that SF and S HNP1-3 are promising biomarkers for distinguishing inflammatory from non-inflammatory joint diseases.
Keywords: peptidové fragmenty; synoviální tekutina; Interleukin-6; lipopolysacharidové receptory; biologické markery; Peptide Fragments; C-reaktivní protein; Enzyme-Linked Immunosorbent Assay; Synovial Fluid; lidé; Biomarkers; C-Reactive Protein; alpha-Defensins; alfa-defensiny; Humans; ELISA; Lipopolysaccharide Receptors; interleukin-6